2006
DOI: 10.1001/archopht.124.7.995
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Fish Consumption, Omega-3 Fatty Acid Intake, and Associations With Age-Related Macular Degeneration

Abstract: To evaluate modifiable risk and protective factors for age-related macular degeneration (AMD) among elderly twins. Methods:The US Twin Study of Age-Related Macular Degeneration comprises elderly male twins from the National Academy of Sciences-National Research Council World War II Veteran Twin Registry. To determine genetic and environmental risk factors for AMD, twins were surveyed for a prior diagnosis of AMD and underwent an eye examination, fundus photography, and food frequency and risk factor questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
252
5
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(269 citation statements)
references
References 40 publications
(46 reference statements)
9
252
5
3
Order By: Relevance
“…8,9,49,50 This cross-sectional study found that higher vitamin D levels are not associated with decreased prevalence of AMD, as expected by the above evidence.…”
Section: Eyesupporting
confidence: 69%
“…8,9,49,50 This cross-sectional study found that higher vitamin D levels are not associated with decreased prevalence of AMD, as expected by the above evidence.…”
Section: Eyesupporting
confidence: 69%
“…13 The AREDS study demonstrated that daily supplementation with antioxidant reduced the risk of developing advanced AMD by 25% at 5 y. Epidemiological studies have suggested a protective role of n-3 PUFAs for developing AMD. [37][38][39][40][41][42][95][96][97] Also, subgroup analysis from the Nutritional AMD Treatment 2 Study from 2013, revealed that high levels of n-3 PUFAs in red blood cells can prevent AMD progression. 98 To assess if antioxidants and n-3 PUFAs could induce additive effects, a second AREDS2 study was designed to evaluate if inclusion of n-3 PUFAs to the AREDS formulation further reduced the risk of progression to advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Epidemiological studies indicate an inverse correlation between dietary intake of fish and the risk of developing AMD. [37][38][39][40][41][42] The disease preventive effects of increased fish intake have been associated with the content of marine omega-3 polyunsaturated fatty acids (n-3 PUFAs). 43 Deficiency of n-3 PUFAs in photoreceptors is associated with the development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…18D). In addition to inflammatory stressors, smoking, an environmental factor shown to greatly increase risk of AMD (Seddon et al, 2006a;Seddon et al, 1996), has been reported to increase serum levels of activated complement factors C3 and B (Robbins et al, 1991;Chao et al, 1982). Thus, stimuli that cause complement accumulation and activation conceivably may stress a system that is not regulated efficiently or effectively and increase the risk of neovascular AMD formation through upregulation of VEGF.…”
Section: Stimuli For Neovascular Amd and Vegf Expressionmentioning
confidence: 99%